Digital mythic genealogies in patriarchal Anglophone horror narratives: feminine hybris and Wiki-oracle nemesis in Annora Petrova creepypasta - Yagüe-Pasamón, Sergio (Amaltea. Revista de Mitocrítica, 2026)
This paper explores Annora Petrova epistolary creepypasta as a gender technology that conceptualises feminine agency as a communal threat. The intersection of myth-critical analysis and feminist close reading allows mapping recurrent mythemes and constellations, as Genesis Eve’s access to forbidden knowledge, the hybris ascent and nemesis corrective punishment. The Wiki-oracle embodies an authorised truth regime that prescribes an inescapable punitive end. Femininity’s self-incriminating voice operates as biopower ventriloquism to legitimise the cruelty pedagogy of violence against femininity, the stigmatisation and ostracism of the scapegoat, and the expulsion from paradise. Thus, canonical Anglophone viral narratives endure disciplinary mythemes.